Gains from coordination in milkfed dairy in Punjab - Gupta, Kanupriya; Roy, Devesh (Emerald Publishing Limited, 2012)
The purpose of this paper is to provide an assessment of benefits to farmers from vertical coordination in dairy. To analyze this, the authors first document the functioning of the cooperative (and changes thereof with increased competition). The paper also uses a field survey to quantify the benefits. In the process, the authors investigate the issue of selection/participation of farmers.This paper is largely based on a survey of households in two districts of Indian Punjab along with secondary data. Descriptive as well as regression analyses have been conducted to address the research questions.The paper presents several key findings. First, the public sector enterprise has been dynamic as competition from private sector has brought favorable changes. There is also evidence of negative selection of farmers implying that those who join dairy cooperatives would have significantly inferior outcomes outside vis‐à‐vis the ones who actually are independent. No bias against farmers by their herd size and significant gains upon participation can explain the scaling up from the demand side. In other words many farmers would find it profitable to become members of the cooperative.Although the survey was extensive in measurement of costs by including variable and fixed costs of production, marketing as well as transaction costs, the data on fixed costs turned out to be noisy. Further, the analysis based on cross‐sectional data could not account for unobserved farmer level individual heterogeneity. Also, the outside option for the farmer in this paper is to be independent. It is possible that this could be integration with private sector, a case that the study does not cover.Benefits from coordination should motivate policies for promoting it. The finding that increased competition has fostered dynamism in the public sector has implications far beyond the case studied here.Despite the extensive system of cooperatives, there do not exist rigorous studies that assess the gains to farmers from this type of horizontal and vertical coordination. The extent of gains establishes a measure of foregone earnings since the supply chains in India remain uncoordinated.